Isoenzyme Polymorphism and Genetic Structure of Ochlerotatus taeniorhynchus (Diptera: Culicidae) in Populations from the Colombian Atlantic Coast (2009)
Ochlerotatus (previously Aedes) taeniorhynchus Wiedemann, 1821, is an efficient vector of the epidemic-epizootic Venezuelan equine encephalitis virus (VEEV) (Forattini 1965; Brault et al. 2004). This mosquito is broadly distributed on the American continent, from Massachusetts in the USA to Santa Catarina in southern Brazil on the Atlantic coast and from California in the USA to Peru on the Pacific coast (Forattini 1965). It is distributed on both the Atlantic and Pacific coasts of Colombia. Although it has been detected in the interior of the country, in Ambalema (Tolima department) (Olano 1985), there is no current evidence of its presence. The last epidemic-epizootic outbreak of VEEV in Colombia occurred in 1995, on the Colombian–Venezuelan frontier, causing the death of an undetermined number of horses and at least 26 people. The mosquitoes chiefly involved in the transmission of the pathology in this area of the Colombian Atlantic coast were found to be O. taeniorhynchus and Psorophora confinnis (Rivas et al. 1997). (Tomado de la introducción)